Development and application of specific questions to classify a child as food texture sensitive. Issue 1 (5th September 2021) - Ross, Carolyn F.; Surette, Victoria A.; Bernhard, Charles B.; Smith‐Simpson, Sarah; Lee, Jookyeong; Russell, Catherine G.; Keast, Russell
Abstract: Understanding food texture sensitivity in children is important in guiding food selection. The objective of this work was to develop a short questionnaire that could be completed by parents in nonclinical settings to provide a categorization for food texture sensitivity in children. This study evaluated the distribution of children as texture sensitive (TS) or non‐texture sensitive (NTS) and the predictive validity of these questions to explain rejection of specific food textures. Three sets of survey data were examined, including data from a home‐use test (HUT) in children with and without Down syndrome (DS), and lingual tactile sensitivity measured by grating orientation task (GOT). From three parent‐completed surveys, the use of the questionnaire yielded a similar distribution of children in the TS category (16–22%) as previously reported. TS children (4–36 months) were more likely to reject specific food textures, including chewy, hard, lumpy, and " tough meat " ( p < .05). A higher percentage of children with a diagnosis of DS were TS (36.9%). Children who were TS showed increased negative behaviors to foods and ate less than NTS children. In older children (5–12 years), TS children were fussier than NTS children ( p < .001). Lingual tactile sensitivity was not significantly different by TS/NTS categorization ( p = .458). This study demonstrated that the use of these five questions specific to food texture provides a useful tool in categorizing a child as TS/NTS, with this information being useful in selecting preferred food textures. Future studies involving these TS questions should perform psychometric assessments and measures of criterion validity using other questionnaires.